Quality Improvement Virtual Practicum: The QI Simulator - Christopher Worsham; Lakshman Swamy; Amir Gilad; Jodi Abbott (Association of American Medical Colleges, 2018)
Introduction In recent years, undergraduate and graduate medical education has been rightfully emphasizing education in quality improvement and patient safety (QIPS). However, the best methods for teaching the foundational principles of QIPS and associated skills are unknown. Methods In collaboration with the Institute for Healthcare Improvement Open School, we developed an approachable simulation for teams of health care trainees at any level and any discipline. The simulation is based on the investigation of a case regarding a psychiatric patient admitted to a fictional hospital for medical treatment who has eloped. In teams, participants investigate the incident by collecting data and using basic QI principles to brainstorm and design interventions. Participants are guided through this paper-based simulation by QI facilitators who have working knowledge of basic QI principles and techniques. Results The simulation has been successfully used with hundreds of medical students and other health professional trainees. While working in teams, participants gained exposure to patient-safety incident reporting and investigation, process mapping, plan-do-study-act cycles, run charts, intervention design, and interactions with hospital administrators. Surveyed participants reported that they had learned QI principles, gained confidence in their ability to do QI work, and increased their likelihood of leading a QI initiative in the future. Discussion Simulation has become a standard way to teach many clinical topics in undergraduate and graduate medical education, and QIPS should be no exception. This simulation has been shown to be effective in increasing understanding of and interest in QIPS.